Guided training has a beneficial effect on umbilical cord blood sampling quality. (November 2021) - Kugelman, Nir; Bart, Yossi; Sghier, Amir; Kedar, Reuven; Bardicef, Mordehai; Lavie, Ofer; Zilberlicht, Ariel; Sagi-Dain, Lena; Damti, Amit
Abstract: Objective: Umbilical cord arterial blood gas analysis is important for neonatal assessment at birth, particularly for determining asphyxia. In April 2019, our labor ward faculty held systemic teaching sessions for midwives, aimed to describe and to exercise proper sampling from both the umbilical cord artery and vein, to ensure biological validity of the values obtained. Our aim was to estimate the rates of inadequate umbilical blood sampling and to evaluate the effect of guided training on the quality of sampling. Study design: This retrospective interventional cohort study included all the women admitted to the delivery room, with a record of postpartum umbilical cord blood sampling. Umbilical cord sampling was considered adequate if two measurements were recorded with a veno-arterial pH gradient of at least 0.02 and an arterio-venous pCO2 gradient of no less than 0.5 kPa. Rates of inadequate sampling were compared between women who gave birth in the year preceding and the year following the guidance. Clinical characteristics were compared between the groups of adequate and inadequate sampling. Results: Overall, 3, 779 women gave birth in the year preceding guidance, and 3, 649 in the subsequent year. Of these, 1, 112 (29.4%) and 1, 105 (30.2%), respectively, underwent umbilical sampling. In the year following the guidance, 750 (67.8%) adequate samples were drawn compared to 692 (62.2%) prior the guidance. This difference demonstrated significant improvement (OR 1.28, 95% CI 1.07–1.52, P = 0.006) in umbilical vessel sampling. Following multivariate logistic regression, inadequate sampling was associated with newborn weight below 2500 g (aOR 1.6, 95% CI 1.2–2.1, p = 0.001), spontaneous vaginal delivery with a possible fetal metabolic abnormality (aOR 2.2, 95% CI 1.7–2.7, p < 0.001), and vacuum deliveries (aOR 1.9, 95% CI 1.5–2.5, p < 0.001). Conclusions: Guided training of proper umbilical blood sampling may reduce the rate of inadequate postpartum blood gas results. Labor wards should consider carrying out annual demonstrations of proper umbilical blood collection, with emphasis on factors that affect the quality of the samplings.